2013
DOI: 10.1038/nature12267
|View full text |Cite
|
Sign up to set email alerts
|

Elastic energy storage in the shoulder and the evolution of high-speed throwing in Homo

Abstract: Although some primates, including chimpanzees, throw objects occasionally1,2, only humans regularly throw projectiles with high speed and great accuracy. Darwin noted that humans’ unique throwing abilities, made possible when bipedalism emancipated the arms, enabled foragers to effectively hunt using projectiles3. However, there has been little consideration of the evolution of throwing in the years since Darwin made his observations, in part because of a lack of evidence on when, how, and why hominins evolved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
158
0
3

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 230 publications
(174 citation statements)
references
References 33 publications
3
158
0
3
Order By: Relevance
“…3). This gradual shift in spine and glenoid angle affects the fiber orientation of the pectoral and scapular muscles, altering the position of the upper limb where force production is optimized (34). The reduced, caudally shifted angle in Homo is consistent with both a decreased reliance on use of the upper limb for overhead actions, such as climbing, and the increased use of…”
Section: Discussionmentioning
confidence: 85%
“…3). This gradual shift in spine and glenoid angle affects the fiber orientation of the pectoral and scapular muscles, altering the position of the upper limb where force production is optimized (34). The reduced, caudally shifted angle in Homo is consistent with both a decreased reliance on use of the upper limb for overhead actions, such as climbing, and the increased use of…”
Section: Discussionmentioning
confidence: 85%
“…Wilk et al (Wilk et al, 1993) argued that throwing athletes enhance torque production by 'pre-stretching' numerous throwing muscles just prior to their activation, resulting in elastic energy storage in the muscle itself. In addition, Roach et al (Roach et al, 2013) found that the posture of the 'cocked' arm (externally rotated) just prior to the rapid shoulder internal rotation motion passively stretches elastic elements crossing the shoulder. By comparing actual power production during throwing to modeled maximum power values for all muscles potentially involved, they inferred that passive stretching results in significant amounts of elastic energy being stored and released, powering the rapid internal rotation of the humerus that follows.…”
Section: Research Articlementioning
confidence: 99%
“…This should significantly reduce torso rotation angular velocity, torque, power and work. These reductions, however, are expected to be modest because we are limiting rotational motion only between the vertebrae and not at the hips.Hypothesis 2: torso rotation primarily powers the storage of elastic energy at the shoulder Roach et al (Roach et al, 2013) proposed that by abducting the shoulder and flexing the elbow as torso rotation reaches its peak …”
mentioning
confidence: 99%
“…The final changes (e.g. fully lateral glenoid position) that enhanced the storage and release of elastic energy in the shoulder to enable high-speed throwing appeared in H. erectus 2 Mya (Roach et al, 2013). Ballistic throwing would have provided H. erectus with enhanced hunting ability and possibly knapping efficiency.…”
Section: Dedicated Tool Manipulation Morphologymentioning
confidence: 99%